NCL-7, a novel all silica analog of polymorph B rich member of BEA family: synthesis and characterization - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
{Polymorph B-rich BEA type structure, NCL-7, was synthesized using hydrothermal method in fluoride medium using perchloric acid as promoter. The samples were characterized using XRD, low temperature N-2-adsorption and Si-29 MASNMR. As the structure of beta is highly disordered Rietveld refinement of powder XRD patterns is precluded. Phase composition is derived using the simulated patterns for the random intergrowths of polymorph A and B by DIFFaX. The stacking direction c' is perpendicular to the a'b' plane of the layer. The composition of polymorph B is found to be ca. 60-65%. Two other structures namely NCL-5 and NCL-6 with varying degree of polymorph B enrichment were also synthesized. Synthesis parameters such as effect of H2O/SiO2, TEAOH/SiO2, HClO4/SiO2 and crystallization temperature were studied thoroughly. The present article explains for the first time the synthesis and characterization of NCL-7, an analog of BEA type family with enrichment of polymorph B and its comparison with normal beta (*
International Symposium on Zeolite and Microporous Crystals (ZMPC 2006), Yonago, JAPAN, JUL 30-AUG 02, 2006
Keywords: B-polymorph; DIFFaX; Promoter; Reitveld refinement; synthesis; zeolite beta

New microporous MOF material based on Zn(II)-polycarboxylate coordination polymer synthesized with the aid of 1,6-diaminohexane as template - Chandra, Debraj; Kasture, Mahesh W.; Bhaumik, Asim (Microporous and Mesoporous Materials, 2008)
A new microporous metal-organic framework (MOF) material ZBTEC-1 has been synthesized by designing infinite coordination polymer network formed between Zn(II) and 1,2,4,5-benzenetetracarboxylic acid (BTEC) under solvothermal conditions in the presence of 1,6-diaminohexane (DAH) as a single molecule template. Powder XRD data demonstrate that the ZBTEC-1 material has a new MOF structure. N-2 sorption studies indicated moderately good surface area (306 m(2) g(-1)) with large size micropores (average pore diameter ca. 0.7 nm) and very high pore volume (1.93 ccg(-1)). C-13 solid state MAS-NMR, FT-IR and UV-visible spectroscopic studies showed the presence of BTEC moieties in the framework. TEM and FE-SEM analysis indicated 30-60 nm diameter size microporous spherical particles for the ZBTEC-1 crystallites. This novel MOF material showed good hydrogen adsorption capacity at 77 K, indicating its potential application in hydrogen storage. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Coordination polymer; Metal-organic framework; Microporous material; porosity; Zinc complex